Уроки технологии в начальных классах: современные методики, проблемы и перспективы - Galushko I. G. (Digitalization in the education system: best practices and implementation practices, 2024)
The purpose of this research is to analyze and develop primary school environmental science lessons, taking into account modern methodologies, identifying challenges, and outlining the prospects for developing this educational field. The work is expected to shed light on the key aspects of teaching and the learning process.
Keywords: педагог; методика; технологии; начальная школа; практическая деятельность; уроки; educator; technologies; methodology: primary school; lessons; practical activities